Sedimentasi Batubara dan Karakteristik Mikroskopis Sulfur Batubara Daerah Sangatta, Kalimantan Timur - Basuki Rahmad Rahmad (Retii, 2020)
The location of research is in Sangatta, East Kalimantan. The coal bearing formation in the Sangatta area is the Balikpapapn Formation of Middle Miocene. The presence of the number of coal seams in Sangatta is repeated until it reaches the number of more than ten coal seams (multiple seams). This condition is strongly influenced by the depositional environment in which the coal is deposited. The method of data collection is carried out directly on the coal outcrops on the walls of the coal mine, using mapping methods and stratigraphic measurements The coal sedimentation of Sangatta area is generally deposited in the delta plain environment, where the prograded delataic process is intensive in the deltaic system. The rapid prograded generally occurs in delta plain environments, with this prograded causing the development or growth of a delta, so that a lot of coal seams are produced. Coal-bearing sediments consist of four types of deposits: channel deposits, spaly deposits, levee deposits and overbank deposits. Seawater tidal in the delta plain, will bring out the sulfate ions through the tidal channel into the coal swamp, forming pyritic framboidal sulphur in the coal in Sangatta area.